ANALISIS KESENJANGAN KUALITAS PELAYANAN TERHADAP KEPUASAN MAHASISWA FAKULTAS HUKUM UNIVERSITAS KATOLIK SANTO THOMAS NEDAN - Saragih, Nawary (Jurnal Manajemen dan Bisnis, 2015)
The purpose of this study was conducted to determine the effect of service quality on student satisfaction Faculty of Law of the Catholic University of Santo Thomas Medan. The sampling technique used is sampling method with a sampling error where sampling based on certain criteria that active students by year of entry proportionally. The data collection is done by using questionnaire data of closed and open (sharpness analysis). Hypothesis analysis is done by using multiple regression analysis and gap analysis. Obtained multiple linear regression equation Y = -6,107X1 0,229X2-4,202X3 + + + 4,317X5 0,503X4. This means that the quality of service (responsiveness, empathy and tangible) positive effect on student satisfaction. While the reliability of service quality assurance, a negative effect on satisfaction Faculty of Law of the Catholic University of Santo Thomas Medan. Interval kesenjanagan Student dissatisfaction is in the interval -337 up to 267 to satisfaction of students, it is necessary to repair the reability (accuracy, speed of service, timeliness in and out perkukliahan. Kesuaian service with the promise offered) and assurance (Alertness Employees in serving the student affairs , Alertness Lecturer in serving the student affairs). In terms of reliability assurance negative influence on satisfaction of students and gap interval in the interval -337 up to 267 to satisfaction of students, efforts are needed improvement to reability and assurance in the hope to close the gap between perceived to increase student satisfaction